Performance Evaluation of Education Infrastructure Public–Private Partnership Projects in the Operation Stage Based on Limited Cloud Model and Combination Weighting Method - Junhao Ma; Xiangjun Li (Buildings)
Due to inappropriate operational strategies, the operational outcomes of education PPP projects often fail to meet expected goals, posing challenges to the sustainable operation of these projects. Through an operational performance evaluation, deviations between operational outcomes and intended goals and the underlying causes of these deviations can be identified, thereby supporting the adjustment of operational strategies. Therefore, this study proposed a performance evaluation model based on the Limited Cloud Model for education PPP projects. Firstly, this study refined the evaluation dimensions of the Balanced Scorecard based on the stakeholder needs and the Asset-Classified Operation characteristics of education PPPs, and an indicators system for the operational stage was developed. Secondly, a performance evaluation model was constructed using the COWA-Critic-Game Theory weighting method and the Finite Cloud Model. Finally, the performance evaluation model was applied to a newly operated university PPP project in Yantai, China, to conduct a case study. The evaluation results demonstrated the practicality and superiority of the proposed model in addressing the complex performance management challenges of education PPPs. This model assisted Special Purpose Vehicles (SPVs) in identifying issues within operational strategies and making necessary adjustments.